1972
DOI: 10.1071/bi9720657
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Dry Matter and Nitrogen by Grains in Different Positions of the Wheat Ear as Influenced by Shading and Defoliation

Abstract: The order of priority for supply of assimilate and nitrogen between individual grains of the wheat ear was studied by determining their accumulation of dry matter and nitrogen when the supply was varied by shading and defoliation, alone and combined, from 2 weeks after anthesis.The production of assimilates by untreated plants was surplus to the requirements of grain filling. Treatments influenced the distribution of dry matter so as to minimize effects on grain.In one cultivar, there was no well-defined patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

1972
1972
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 8 publications
5
46
1
Order By: Relevance
“…The 24-hr harvest of the shaded ear treatment of experiment 3b (in which flag leaves were fed) gave relative activities for a, b, and c of 100,117 and 87 respectively. Rawson and Evans' (1970) labelling studies and Bremner's (1972) grain growth studies also show that grain b gets more shoot assimilate than others.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 24-hr harvest of the shaded ear treatment of experiment 3b (in which flag leaves were fed) gave relative activities for a, b, and c of 100,117 and 87 respectively. Rawson and Evans' (1970) labelling studies and Bremner's (1972) grain growth studies also show that grain b gets more shoot assimilate than others.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed we may infer from experiment 3b and a number of others done in similar conditions (e.g. Rawson and Evans 1970;Bremner 1972) that grain growth was not limited by the availability of assimilate from any source, but by the capacity of the grains to utilize assimilate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kernel sink strength is related to location in the spike, where kernels in central spikelets, or basal kernels within a spikelet, have greater sink strengths (Fig. 5, Rawson and Evans, 1970;Bremner, 1972). This pattern of sink strength positively correlates with the fertilization pattern.…”
Section: Kernel Growth Submodelmentioning
confidence: 99%
“…There are also varietal differences in N uptake efficiency (Seth et al 1960, Mikesell and Paulsen 1971, Noaman and Taylor 1990. The situation may be affected by leaf shading, which becomes more significant at high plant population densities leading to translocation of N from shaded leaves (Campbell and Read 1968, Willey and Holliday 1971, Bremner 1972). It has also been shown that prolonged root activity and leaf duration positively affect N accumulation into the grain (Spiertz andEllen 1978, Herzog andStamp 1983).…”
Section: Introductionmentioning
confidence: 99%